Implementasi Kemampuan Mengajar Guru PAI Pada SMA Negeri Se- Pangkalpinang - Yusra Jamali; Janawi Janawi (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
Implementation of school level education is determined by the readiness, competence and ability of teachers in managing and controlling learners. This study focuses only on the readiness of teachers of Islamic Education (PAI) in planning, implementing and conducting assessments in the learning process. This study aims to determine the strategy of learning planning, preparation of learning materials, methods of implementation and evaluation techniques by teachers of Islamic Education at SMAN in Pangkalpinang City. This research uses descriptive method with qualitative approach. The results showed that PAI teachers at SMAN had done the planning by containing competency standards, basic competencies, indicators, learning objectives, subject matter, approaches, strategies and learning methods, learning activities, tools / learning resources and assessment. While the method of palembang is more dominant using lectures, discussions, assignments and practices. While the means of assessment use in writing, oral and observation.